1999
DOI: 10.1023/a:1008983215833
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hydrogels are three-dimensional polymeric networks very similar to biological tissues and potentially useful as drug delivery systems. Poly(vinyl alcohol)-based hydrogels containing different amounts of dextran or chitosan were prepared using the freezing-thawing method. Repeated freezing-thawing cycles of a poly(vinyl alcohol) (PVA) aqueous solution lead to the formation of crystallites which act as cross-linking sites, and a hydrogel with a high capacity to swell is obtained. The effects of the two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(30 citation statements)
references
References 12 publications
0
29
1
Order By: Relevance
“…Obtained membranes showed a quick healing rate for incision wounds in rat-model and high exudates capacity, compared to commercial gauzes. PVA-chitosan blend hydrogel membranes as wound dressings were designed for the first time by Cascone et al [39] , using repeated (F-T) cycles. The results revealed that an addition high content of chitosan to membranes prevents the crystalline phase formation of PVA, which affects slightly on the thermal stability and forms porous and filamentous morphological structure.…”
Section: Classification Of Wound Dressingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtained membranes showed a quick healing rate for incision wounds in rat-model and high exudates capacity, compared to commercial gauzes. PVA-chitosan blend hydrogel membranes as wound dressings were designed for the first time by Cascone et al [39] , using repeated (F-T) cycles. The results revealed that an addition high content of chitosan to membranes prevents the crystalline phase formation of PVA, which affects slightly on the thermal stability and forms porous and filamentous morphological structure.…”
Section: Classification Of Wound Dressingsmentioning
confidence: 99%
“…Dextran was formerly utilized for drug delivery and blood plasma polymer expander. Cascone et al [39] developed PVA-dextran hydrogel membranes using F-T crosslinking cycles, showing more ordered and uniform physically crosslinked PVA membranes. This study explored that PVA-dextran membranes possessed more ordered membranes structure, good swelling capacity, and adequate release profile due to excellent miscibility degree between PVA and dextran, as compared to PVA-chitosan membranes.…”
Section: Classification Of Wound Dressingsmentioning
confidence: 99%
“…These cycles allow the formation of fine crystalline domains that act as crosslinking sites, leading to the insolubility of hydrogels into the water. An advantage of this technique when compared with other chemical‐based hydrogels' preparation is the nontoxicity behavior of these hydrogels, once it is free of residual chemical from the conventional crosslinker agents, besides an improvement of mechanical strength 6…”
Section: Introductionmentioning
confidence: 99%
“…Atactic PVA physical hydrogels have also been prepared in the presence of biopolymers, especially polysaccharides, in order to improve their biocompatibility and introduce a bioactive component 12–18. In this case a semi‐interpenetrating polymer network (semiIPN) is formed if the biopolymer does not interfere with PVA hydrogen bonded network formation.…”
Section: Introductionmentioning
confidence: 99%